Determinan faktor yang mempengaruhi minat investasi - Purwantini, Maria; Yustrianthe, Rahmawati Hanny; Grediani, Evi; Handayani, Handayani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Investment is a type of investment in which investors hope to make a profit. In general, investors invest to improve the quality and welfare of their lives through the profits and returns they receive. The research is intended to empirically test the factors that influence investment intentions. These factors include capital market training, investment knowledge, and the benefits of investing in equities. The population of this study was 121 students in Yogyakarta who had attended capital market training. Samples were taken by the convenience sampling method. A questionnaire was used to collect data. Multiple linear regression was used to analyze the data. The results of this study show that capital market training has a proven influence on investment intentions. Investment knowledge has an effect on investment intention, and investment benefits have an effect on investment intention received.